1993
DOI: 10.1002/jcp.1041550209
|View full text |Cite
|
Sign up to set email alerts
|

CSF‐1 control of C‐FMS expression in normal human bone marrow progenitors

Abstract: We have previously shown (Zhou et al: Blood, 72:1870, 1988) that IL3, added with low concentrations of CSF-1 (1 ng/ml) to normal human CD34+ enriched cells, promoted the development of various types of colonies including those containing immature monocytes. However, when high concentrations of CSF-1 (20 ng/ml) were added alone or together with IL3, smaller colonies with mature macrophages were found. Here we show by in situ hybridization that IL3 allows the development, from CD34+ cells, of a subpopulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Expression of the M-CSF receptor is very low in hematopoietic stem cells and increases as the cells begin to differentiate (37)(38)(39). Premature expression in early progenitors may cause aberrant proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the M-CSF receptor is very low in hematopoietic stem cells and increases as the cells begin to differentiate (37)(38)(39). Premature expression in early progenitors may cause aberrant proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Early myeloid cells make very little M-CSF receptor mRNA compared with mature cells (37)(38)(39) that have not yet been identified would be altered due to the expression of the t(8;21) fusion protein, AMLl-ETO. Further studies will be necessary to identify these target genes and also elucidate the mechanism by which AMLl-ETO exerts its effects.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the low concentrations of cytokines used in these studies were necessary to avoid down-regulation of some receptors on immature cells (6). These low concentrations of cytokines were always found equally optimal for bone marrow and umbilical cord blood early progenitors.…”
mentioning
confidence: 85%
“…The complete procedure is based on the methods described by Angerer et al (1987) and Bernaudin et al (1988) and has been detailed extensively in previous reports (Panterne et al, 1993. The p21 cip1 probe is a 0.6-kb HindIII/XbaI insert in a RC/CMV plasmid (In Vitrogen), a generous gift of Dr. J. M. Blanchard, Montpellier, France.…”
Section: Ishmentioning
confidence: 99%
“…Because most adult human hematopoietic CD34 ϩ progenitors are in the G 0 /G 1 phase (Gothot et al, 1997), we were interested in how p21 cip1 mRNA was regulated when quiescent cells became competent to go through the cell cycle and what the effect of TGF-␤1 on p21 cip1 mRNA modulation was. Because these primitive cells usually express low levels of mRNA or proteins controlling their growth, such as cytokine receptors Gothot et al, 1997), we have used a sensitive and semiquantitative in situ hybridization (ISH) method developed in our laboratory which permits the detection of a few mRNA copies in single isolated progenitors (Panterne et al, 1993. Our results demonstrate that the CDKI p21 cip1 is not only regulated in differentiating cells (Steinman et al, 1998;Taniguchi et al, 1999), but also in primitive undifferentiated pro-genitors to control exit from quiescence.…”
mentioning
confidence: 96%